Influence of Shared Knowledge and Communication Timeliness on Nurse and Doctor Collaboration and Inpatient Safety in a Regional Public Hospital - Wa Ode Harsen; Sartini Risky; Asbath Said (Waluya The International Science of Health Journal, 2026)
Introduction: The implementation of interprofessional communication collaboration between health workers at the Regional Public Hospital in Kendari City has not been carried out properly because there are still ineffective communication skills such as the implementation of Situation, Background, Assessment, Recommendation (SBAR) confirmation, the accuracy of doctor visits so that there are differences of opinion between health workers in carrying out teamwork. Therefore, researchers conducted a study on influence of shared knowledge and communication timeliness on nurse and doctor collaboration and inpatient safety in a Regional Public Hospital. Method: This study is a correlational analysis using a cross-sectional approach. The population was 286 health workers, where the sample selection was carried out using the Proportionate Stratified Random Sampling method. The research sample was 98 health workers. The measuring instrument used was a questionnaire. The data analysis used was chi square analysis. Result: The effect of knowledge sharing (ρ=0.000) and timeliness (ρ=0.001) in the implementation of effective communication in interprofessional collaboration between nurses and doctors on the safety of inpatients at the Regional Public Hospital in Kendari City. Conclusion: There is an influence of knowledge sharing and timeliness in the implementation of effective communication in interprofessional collaboration between nurses and doctors on the safety of inpatients at the Regional Public Hospital in Kendari City.